1995
DOI: 10.1177/107110079501601106
|View full text |Cite
|
Sign up to set email alerts
|

Early Motion After Repair of Achilles Tendon Ruptures

Abstract: The purpose of this study was to evaluate the clinical outcome of patients treated with limited immobilization and early motion after repair of acute Achilles tendon ruptures. Thirteen consecutive patients with complete ruptures of the Achilles tendon were identified, repaired, and rehabilitated with early motion starting an average of 10 days after surgery. Active range of motion was begun at an average of 23 days and weightbearing in a walking boot was started at an average of 3.5 weeks after surgery. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 9 publications
0
36
0
3
Order By: Relevance
“…4,7,14,15,17,18 In these studies, calf muscle strength has been measured postoperatively in patients with total Achilles tendon ruptures. We have recently, in two prospective studies on patients with chronic Achilles Vol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,14,15,17,18 In these studies, calf muscle strength has been measured postoperatively in patients with total Achilles tendon ruptures. We have recently, in two prospective studies on patients with chronic Achilles Vol.…”
Section: Discussionmentioning
confidence: 99%
“…10 There are only a few studies on calf muscle strength in patients with Achilles tendon disorders. Calf muscle strength has been measured after rehabilitation in patients with surgically treated complete Achilles tendon ruptures 4,14,15,17 and in patients with complete Achilles tendon ruptures treated either surgically or nonsurgically. 7,18 We have recently, in two prospective studies on middle-aged recreational athletes with chronic Achilles tendinitis/tendinosis, reported the results of surgical treatment followed by 6 weeks of immobilization and of surgical treatment followed by 2 weeks of immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…7,1o,12,15,18,2o These studies have reported no reruptures (one report of a partial rerupture), but have also reported minor (superficial wound infections, sensory loss, and tendocutaneous adhesions) or major surgical (deep infection and pulmonary embolus) complications. ' , 10,11,12,15,18,19,20 The current study was designed to: 1. evaluate the clinical results of repair of acute ruptures of the Achilles tendon utilizing the triple bundle technique 9,10,16,21 followed by early ankle range of motion exercises, and 2. compare these results to nonoperative cast treatment with delayed ankle range of motion exercises.…”
Section: Introductionmentioning
confidence: 99%
“…10,27 En nuestro protocolo, la carga y la movilidad se retrasaron, por precaución, en el posoperatorio de los pacientes tratados con técnica percutánea, a diferencia de lo publicado por Amlang y cols. 4 con respecto a la escala funcional de la AOFAS, cretnik y cols.…”
Section: Discussionunclassified